Use of ChatGPT by the Library and Information Science Students at the University of Delhi - Margam, Madhusudhan; Pandey, Parbati; Bharti, Ravindra Kumar (DESIDOC Journal of Library & Information Technology, 2025)
This study explores the use of ChatGPT among Library and Information Science (LIS) students at the University of Delhi. A structured online survey with 13 questions (both closed and open-ended) was conducted via Google Forms in March 2024. The survey link was shared through the official WhatsApp group for BLISc and MLISc students of the University of Delhi’s Department of Library and Information Science, as well as individually through personal WhatsApp accounts of the 2023-2024 academic year, yielding a 79.36 % response rate from 100 participants. Descriptive statistical analysis of the data revealed that ChatGPT is widely recognised. Students primarily use ChatGPT for assignments, valuing its free access, quick responses, and idea-generation capabilities. Most respondents find its information somewhat accurate (61.9 %), and 66 % are likely to recommend it for academic purposes. The most cited advantage (67 %) is its free, 24/7 availability. However, 56.3 % are concerned about over-reliance on AI. Additionally, 89.7 % note the absence of institutional policies on AI use, and 85.6 % have yet to receive faculty recommendations to use ChatGPT for academic or research work to ensure academic and research integrity. The findings will aid the university in developing policies to integrate AI tools in academia effectively.